Theoretical proposal of steps for the implementation of the Industry 4.0 concept - Cordeiro, Gabrielly Araújo; Ordóñez, Robert Eduardo Cooper; Ferro, Rodrigo (Brazilian Journal of Operations & Production Management, 2019)
Goal: The purpose of this paper is to present a proposal of steps for the implementation of Industry 4.0 in the industrial context, considering management and operational aspects. The reason is to discuss that technological change is accompanied by many organizational implications, in which it is perceivable that some companies already experience strategic and operational turbulence due to the lack of understanding of the this structure’s complexity. Design / Methodology / Approach: This study assumes an exploratory character because the subject of analysis is still in the knowledge-structuring phase. In this sense, data was collected from the literature review. Results: A theoretical proposal for the Industry 4.0 implementation framework is presented in flow format. It is organized in steps that cover the strategic and operational aspects during the implementation flow. Limitations of the investigation: The limitations of this study are directly related to its theoretical nature and the difficulty of finding tools that help in the execution of each proposed stage. Practical implications: However, based on theoretical insights, a trajectory of a transformation model is proposed, thus this research intends to show clearly and direct how companies can introduce the aspects of Industry 4.0 to their own benefit. Originality / Value: In this study, a conceptual model is structured, and it indicates a potential of application because it contributes to support and encourage the adoption of technologies and concepts indicated in the Industry 4.0 literature in a structured way.